2023
DOI: 10.1039/d3ra05531k
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, molecular docking and DFT studies on novel melatonin and isatin based azole derivatives

Keshav Kumar Saini,
Ravindra Kumar Upadhyay,
Ravi Kant
et al.

Abstract: In order to address the pressing demand for newer broad-spectrum antifungal medicines with enhanced activity, computer modelling was utilised to rationally develop newer antifungal azole-based drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…These results reveal the importance of substitution on benzene ring and presence of thiosemicarzaone scaffold on the isatin–triazole hybrid for enhanced binding interaction of the drug molecules which is also supported by the literature. 22,109 Molecular docking results are in good agreement with the findings of DFT analyses and these computational explanations suggested that the synthesized thiosemicarbazones of isatin–triazole hybrids may act against PI3K as anti-cancer agents.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…These results reveal the importance of substitution on benzene ring and presence of thiosemicarzaone scaffold on the isatin–triazole hybrid for enhanced binding interaction of the drug molecules which is also supported by the literature. 22,109 Molecular docking results are in good agreement with the findings of DFT analyses and these computational explanations suggested that the synthesized thiosemicarbazones of isatin–triazole hybrids may act against PI3K as anti-cancer agents.…”
Section: Resultssupporting
confidence: 76%
“…Obtaining the structural parameters from the optimized geometry of the synthesized molecules that lead to the information of molecular interactions is considered as preliminary step before molecular docking analyses. 22 In this context, the Density Functional Theory (DFT) calculations, specically the 6-311G (d,p) basis set at the B3LYP level were carried out. [57][58][59] The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) are two popular quantum chemical parameters.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have documented hybrid molecules that have undergone clinical or preclinical validation, offering promising prospects for the creation of safer and more effective drugs to combat a wide array of diseases. [1][2][3][4][5] Over 75 % of FDA-approved drugs contain heterocyclic units, with nitrogen-containing heterocycles being the most common. [6] Molecular hybridization, which involves combining two pharmacophoric moieties to create a novel therapeutic molecule, is a useful strategy in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds hold significant relevance across diverse scientific domains, encompassing medicinal chemistry and biochemistry. Numerous reports have documented hybrid molecules that have undergone clinical or preclinical validation, offering promising prospects for the creation of safer and more effective drugs to combat a wide array of diseases [1–5] . Over 75 % of FDA‐approved drugs contain heterocyclic units, with nitrogen‐containing heterocycles being the most common [6] …”
Section: Introductionmentioning
confidence: 99%